2023
DOI: 10.1002/ange.202214208
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Charge Transport in a 2D/3D Perovskite Heterostructure by Selecting an Ordered 2D Perovskite as the Passivator

Abstract: We demonstrate that an ordered 2D perovskite can significantly boost the photoelectric performance of 2D/3D perovskite heterostructures. Using selective fluorination of phenyl-ethyl ammonium (PEA) lead iodide to passivate 3D FA 0.8 Cs 0.2 PbI 3 , we find that the 2D/3D perovskite heterostructures passivated by a higher ordered 2D perovskite have lower Urbach energy, yielding a remarkable increase in photoluminescence (PL) intensity, PL lifetime, charge-carrier mobilities (ϕμ), and carrier diffusion length (L D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…To verify this conjecture, we first examined the conformational information of PEA + with different concentrations of AABr using SFG-VS. As a second-order nonlinear optical technique, SFG-VS is a powerful tool for evaluating molecular symmetry, orientation, and orientational disorder. SFG-VS has been used to probe the molecular orientation of the organic cations of lead-halide perovskites [14][15][16] and the passivator layer capping above the perovskite interface. [17,18] Figure 1b displays the ssp spectra of the phenyl groups of quasi-2D perovskites prepared with different concentrations of AABr.…”
Section: Resultsmentioning
confidence: 99%
“…To verify this conjecture, we first examined the conformational information of PEA + with different concentrations of AABr using SFG-VS. As a second-order nonlinear optical technique, SFG-VS is a powerful tool for evaluating molecular symmetry, orientation, and orientational disorder. SFG-VS has been used to probe the molecular orientation of the organic cations of lead-halide perovskites [14][15][16] and the passivator layer capping above the perovskite interface. [17,18] Figure 1b displays the ssp spectra of the phenyl groups of quasi-2D perovskites prepared with different concentrations of AABr.…”
Section: Resultsmentioning
confidence: 99%
“…This low distortion ratio is ascribed to the orientation and structural ordering of the ADP cations. It was reported that the atoms on the aromatic ring can induce the interlayer interaction between the adjacent organic cations, leading to the reorientations of the organic cations and further influencing the structural ordering of the perovskite inorganic framework . Thus, it is believed that the nitrogen atom on the pyridine can enhance the orientation of the ADP cations and result in a high structural ordering of the perovskite surface with a low distortion ratio, which eventually boosts passivation effects.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the 4F-PEAI-treated sample in Figure 1G exhibits large-size particles (∼400 nm) on (100) facets as well as rough (111) facets, indicating that both (100) and (111) facets are passivated. 23,24 Considering the existence of π electrons in PEAI and 4F-PEAI not in CHEAI, we speculate that the six π electrons delocalized in the aromatic group may act as an electron-donating group to form adducts on (111) facets. 25,26 To further confirm this conjecture, a potassium amyl sulfide (KAS) with an organic sulfide anion (AS − ) was applied on the perovskite surface, and we observed that both (100) and (111) are passivated, as shown in the AFM image in Figure 1H.…”
Section: T H Imentioning
confidence: 89%
“…In recent years, organic–inorganic hybrid perovskite solar cells (PSCs) are becoming a research hotspot in the field of photovoltaic energy, because their certified photoelectric conversion efficiency (PCE) has reached 26.1%, which is equivalent to that of commercial silicon-based solar cells. The realization of this excellent PCE can be attributed to the numerous advantages of perovskite crystals, including broad spectral response, tunable optical band gap, high defect tolerance, small exciton binding energy, long carrier diffusion distance, and so forth. However, the weak binding and ion–electron characteristics of perovskite crystals inevitably cause high-density defects, which leads to significant nonradiation recombination and reduces the overall reliability of the device. , …”
Section: Introductionmentioning
confidence: 99%
“…5−9 However, the weak binding and ion− electron characteristics of perovskite crystals inevitably cause high-density defects, which leads to significant nonradiation recombination and reduces the overall reliability of the device. 10,11 In general, the low-temperature solution preparation process of the perovskite active layer makes it well-compatible with other functional layers and substrates, which endows the PSCs with diverse device architectures and flexible application situations. 12 Nevertheless, the high-density defect states and weak binding generated during this process diminish the resistance to moisture and cause significant energy loss, which is unfavorable to the long-term operation stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%